153k views
3 votes
Solve the system below using substitution write your final answer as a coordinate point

y = -2x + 4
-x + 3y = -9

plz help

1 Answer

2 votes

(3, -2)

Explanation:

y = -2x + 4

-x + 3y = -9

-x + 3 (-2x + 4) = -9

-x + -6x + 12 = -9

-7x = - 9 – 12

-7x = - 21

X = 3

We substitute x with 3 to evaluate y;

-3 + 3y = -9

3y = -6

y = -2

Elimination Method;

y = -2x + 4

-x + 3y = -9

We arrange the equations for substitution;

2x + y = 4

-x + 3y = -9

We multiply the first equation with 3 so we can substract one variable to zero;

3 (2x + y = 4)

= 6x + 3y = 12

Then we subtract the two;

6x + 3y = 12

-x + 3y = -9

7x = 21

x = 3

We evaluate y by substitution x with 3 in one of the equation;

-x + 3y = -9

-3 + 3y = -9

3y = -6

y = -2

The final answer expressed as a coordinate point is;

(3, -2)

User Liam Kernighan
by
4.9k points